Analisis Penentuan Lokasi Program Keluarga Harapan Dalam Menanggulangi Masalah Kekumuhan di Kota Tebing Tinggi, Sumatera Utara - Chairida Yunita Putri; Sirojuzilam Sirojuzilam; Rujiman Rujiman (Jurnal Serambi Engineering, 2020)
Slum is a general impression or picture of attitudes and low behavior seen from the standard of living and middle class income. Communities that live in slums economically are generally classified as poor and low-income groups, which are often the reason for the degradation of discipline and disorder in various social order. This study aims to investigate and determine the right location for Family Hope Program (PKH) implementation so program implementation can be more targeted and targeted and able to reduce and overcome the problem of slums in Tebing Tinggi City, North Sumatra province. The method used is to use spatial analysis with a Geographic Information System (GIS) and 5 indicators data from TNP2K. These indicators are combined and modeled spatially using 3 class locations namely Inaccurate, Less Accurate and Precisely Accurate. The results of spatial analysis and modeling are the location of Inaccurate (Tebing Tinggi Kota sub-district), Less Accurate (Padang Hilir and Padang Hulu sub-district) and Precisely Accurate (Bajenis and Rambutan sub-district). The resulting spatial model was validated with satellite photos from Google Earth and photos of field visits using triangulation validation techniques